Implementasi Kebijakan Sertipikat Tanah Elektronik dalam Konteks Transformasi Digital di Kantor Pertanahan Kabupaten Bintan - Satryadin, Maulana Arba’; Hadna, Agus Heruanto; Putra, R. Ahmad Romadhoni Surya (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2025)
The rapid development of technology and information has driven changes in public sector services, including the adoption of digital innovations to facilitate access to public sector services. In response to these developments, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) has established a policy on electronic land certificates for the public through ATR/BPN Ministerial Regulation No. 3 of 2023, which will be implemented in stages starting in mid-2024. This policy was then prioritized for 104 Land Offices, including the Bintan Regency Land Office through ATR/BPN Ministerial Decree Number 285/SK-OT.01/III/2024. The purpose of this study is to analyze the gap between the design of the electronic land certificate policy and its implementation at the Bintan Regency Land Office, as well as to map the factors that influence the implementation of electronic land certificates at the field level. This study applies a qualitative approach using primary data obtained through interviews with informants and observations, as well as secondary data obtained from journals, data, and other relevant documents. The results of the study on policy implementation show that the implementation of the electronic land certificate policy in Bintan is hampered by a top-down approach that does not take into account the readiness of electronic data in the field. Policy dissemination has not been optimal, and the quality of electronic land data remains a challenge. Factors such as leadership, interoperability, bureaucracy, and digital culture also influence the smooth running of this policy. In practical terms, the findings of this study imply the need for a more participatory policy approach in the implementation of the electronic certificate policy. Public policy innovation must be based on data so that the digital transformation that is carried out can be on target and sustainable in overcoming the real problems of digital bureaucracy in society.